2013
DOI: 10.1186/1742-4755-10-2
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for mode of delivery in nulliparous Argentinean women: a qualitative study

Abstract: BackgroundOver the last three decades, cesarean section (CS) rates have been rising around the world despite no associated improvement in maternal and perinatal mortality and morbidity. The role of women’s preferences for mode of delivery in contributing to the high CS rate remains controversial; however these preferences are difficult to assess, as they are influenced by culture, knowledge of risk and benefits, and personal and social factors. In this qualitative study, our objective was to understand women’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
4
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(95 citation statements)
references
References 18 publications
2
86
4
3
Order By: Relevance
“…51 A qualitative study of women's delivery preferences found that women in a public maternity facility were unaware that the mode of delivery was their choice; instead, they believed it to be a medical decision. 52 These studies reflect the fact that many physicians consider it unnecessary to inform women about their choices or show regard for their needs and preferences. The gender stereotyping exercised by physicians generalizes and pathologizes women's feelings and experiences in a way that strips women of power, decision-making and control over their own bodies.…”
Section: Obstetric Violence As An Unethical Gender Stereotypingmentioning
confidence: 99%
“…51 A qualitative study of women's delivery preferences found that women in a public maternity facility were unaware that the mode of delivery was their choice; instead, they believed it to be a medical decision. 52 These studies reflect the fact that many physicians consider it unnecessary to inform women about their choices or show regard for their needs and preferences. The gender stereotyping exercised by physicians generalizes and pathologizes women's feelings and experiences in a way that strips women of power, decision-making and control over their own bodies.…”
Section: Obstetric Violence As An Unethical Gender Stereotypingmentioning
confidence: 99%
“…Improving the perceived quality of care of women ensures that the facility has the capacity of staff and resources to carry out safely and successfully CS. (Liu et al, (2013). Additional staff friendliness is an important building perceived quality of service not only, but also the choice of mode of delivery Yazdizadeh (2011),…”
Section: Resultsmentioning
confidence: 99%
“…Once the mother has chosen the right service provider, she made sure good professional responsible decisions in which the alternative delivery method would have been chosen as a last resort option to the satisfaction of the mother. Tian et al, (2014) Liu et al, (2013).…”
Section: Introductionmentioning
confidence: 99%
“…The reasons that women choose a vaginal birth include a quicker recovery, the idea that it is healthier for the mother and baby [7,8,10,16], it allows breast-feeding sooner [7,14], it is more natural [7,8,16], it leads to a quicker discharge from hospital [10,14,17], it is less risky [10], and it is on the advice of the doctor or midwife [8].…”
Section: Introductionmentioning
confidence: 99%